Consistent Efficacy of Apremilast in Patients with Psoriasis Regardless of Baseline Disease Severity or Special Area Involvement: Subgroup Analysis from PROMINENT - Masatoshi Abe; Yukari Okubo; Hidetoshi Takahashi; Koki Endo; Siddharth Chaudhari; Cynthia Deignan; Hamid Amouzadeh; Ryosuke Hino (Adis, Springer Healthcare, 2024)
Abstract Introduction Psoriasis involvement in special areas (e.g., scalp or nails) is associated with a great disease burden yet it is often inadequately treated with topical treatments. The efficacy and tolerability of apremilast plus existing topical therapy in Japanese patients with mild to moderate plaque psoriasis were demonstrated in PROMINENT, a phase 3b, multicenter, open-label, single-arm study. We evaluated the efficacy of apremilast across disease severities and special areas involved in these patients. Methods In PROMINENT, patients received apremilast 30 mg twice daily for 16 weeks in addition to their existing topical therapy, with the option of topical therapy reduction at the discretion of their physician while continuing apremilast treatment from Weeks 16 to 32. We performed a post hoc analysis, assessing apremilast efficacy and safety in Japanese patients stratified by baseline static Physician Global Assessment (sPGA) score (2 [mild] or 3 [moderate]) and special area involvement. Results Of patients with baseline sPGA = 2 and sPGA = 3, 62.7% and 30.7%, respectively, achieved sPGA score 0 or 1 at Week 32. At Week 32, improvements in skin, nail, scalp, and quality of life assessments were observed regardless of baseline sPGA score. Improvements in these endpoints at Week 32 were also observed in patients with special area (scalp or nail) involvement (n = 134). Incidence of adverse events was similar between patients with baseline sPGA = 2 and sPGA = 3. Conclusions Apremilast in combination with topical therapy may be a beneficial treatment for Japanese patients, who have limited systemic treatment options for mild to moderate psoriasis or psoriasis in special areas. Trial Registration NCT03930186.